Analysis on a Top Accounting Software for Accountants Enhancing Efficiency and Accuracy - Ullah, Naqeeb; Ijaz, Aamir; Ullah, Aziz; Nawaz, Adil (2023)
The aim of the research was to empirically analyse the most effective accounting software for accountants, specifically in SMEs of UK. For the current research, primary quantitative research method was used, and information were gathered from 100 accountants working in SMEs of UK. For data analysis, descriptive and frequency analysis were used though using SPSS software. Findings revealed that Fresh book, Quick book, Zoho, Wave are mostly used in SMEs of UK. Further, it has also been analysed that Fresh book is one of the most effective accounting software due to higher quality, features, and fastest speed. Findings in the current research has significantly contributed in the information body of accounting sphere, and fill a gap in previous studies.